2018
DOI: 10.1371/journal.pone.0199615
|View full text |Cite
|
Sign up to set email alerts
|

Multiple insecticide resistance in Culex quinquefasciatus populations from Guadeloupe (French West Indies) and associated mechanisms

Abstract: West Nile (WN) virus has been detected in Guadeloupe since 2002. Even if no WN human cases have been detected so far, mosquitoes from Culex genus especially Culex quinquefasciatus are recognized as potential WN vectors in Guadeloupe. To evaluate the impact of local vector control activities on this mosquito species we assessed the resistance levels of Cx. quinquefasciatus populations from three different sites from Guadeloupe (Abymes, Saint François and Gourbeyre) to malathion, temephos and deltamethrin. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…quinquefasciatus mosquito in the area of study would survive from temephos exposure. This result of study in accordance with previous study by Dellanay et al 12 which showed the temephos resistance status of the Tunisian Culex pipiens. This agrees with our results which showing a resistance status of Cx.…”
Section: Discussionsupporting
confidence: 93%
“…quinquefasciatus mosquito in the area of study would survive from temephos exposure. This result of study in accordance with previous study by Dellanay et al 12 which showed the temephos resistance status of the Tunisian Culex pipiens. This agrees with our results which showing a resistance status of Cx.…”
Section: Discussionsupporting
confidence: 93%
“…The Leu/Phe substitution and prior reports of the kdr mutation have been implicated in the development of pyrethroid resistance in several mosquito species, including An. gambiae [32], Culex pipiens pallens [33] and Culex pipiens quinquefasciatus [34, 35]. Previous researches have found high frequencies of 1014F/C and 1014F/S substitutions in An.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results encasing pyrethroid resistance in Cx . quinquefasciatus have been reported worldwide [3235]. Resistance to pyrethroids in Cx .…”
Section: Discussionmentioning
confidence: 99%